Educational Level, Socioeconomic Status, and Interpersonal Communication Competence in Response to Digital Deceptive Messages - Nana Raihana Askurny; Dewi Kusrini (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2026)
This study investigates the correlation between educational level and socioeconomic status in determining individuals' interpersonal communication competence when responding to digital deceptive messages. Utilizing a descriptive quantitative research design, the authors developed a 15-item Likert-scale questionnaire based on authentic fraudulent messages obtained from police investigators in Tanjungpinang and Bintan, Indonesia. Data collected from 120 participants underwent rigorous validity, reliability, and normality testing before being analyzed via multiple regression. The findings reveal that while educational level and socioeconomic status collectively show a significant positive correlation with communication competence, socioeconomic status alone provides a negligible contribution. Specifically, the regression model suggests that higher education levels significantly enhance one’s ability to navigate digital interactions safely, whereas employment status does not significantly alter this competence due to universal smartphone access. This research contributes a predictive framework for identifying cybercrime vulnerability, highlighting that educational background is a more critical factor than wealth or job status in developing the interpersonal metafunctions necessary to detect speech intentions and avoid digital traps.